2015
DOI: 10.1371/journal.pone.0142249
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Thoracic Paravertebral Block Reduces Intraoperative Opioid Requirement and Improves Analgesia after Breast Cancer Surgery: A Randomized, Controlled, Single-Center Trial

Abstract: ObjectivesThe contribution of ultrasound-assisted thoracic paravertebral block to postoperative analgesia remains unclear. We compared the effect of a combination of ultrasound assisted-thoracic paravertebral block and propofol general anesthesia with opioid and sevoflurane general anesthesia on volatile anesthetic, propofol and opioid consumption, and postoperative pain in patients having breast cancer surgery.MethodsPatients undergoing breast cancer surgery were randomly assigned to ultrasound-assisted parav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Our non‐inferiority margin of 0‐100 µg can be considered appropriate as Naik et al observed that a median dose of 350 µg of fentanyl was used in their study comparing dexmedetomidine versus saline . Another study also observed a median difference in intraoperative fentanyl requirement of 150 µg to be non‐inferior between paravertebral block with propofol group and general anaesthesia group …”
Section: Discussionmentioning
confidence: 92%
“…Our non‐inferiority margin of 0‐100 µg can be considered appropriate as Naik et al observed that a median dose of 350 µg of fentanyl was used in their study comparing dexmedetomidine versus saline . Another study also observed a median difference in intraoperative fentanyl requirement of 150 µg to be non‐inferior between paravertebral block with propofol group and general anaesthesia group …”
Section: Discussionmentioning
confidence: 92%
“…This space includes spinal and sympathetic nerves and their block provides effective anesthesia in the management of thoracic and/or abdominal pain after various types of surgery [ 3 ]. The application of PVB has been shown to improve pain scores and decrease analgesic drug requirements, postoperative nausea, and vomiting [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regional anaesthesia has been used and studied extensively in breast surgery as an opioid‐sparing strategy, with block of the intercostal supply by thoracic paravertebral block (TPVB) becoming a popular technique . New fascial plane blocks have been developed as alternative or supplementary techniques for chest wall analgesia, including the pectoral nerve blocks (PECS 1 and PECS 2) and serratus plane block .…”
Section: Introductionmentioning
confidence: 99%